2008
DOI: 10.1200/jco.2008.16.1455
|View full text |Cite
|
Sign up to set email alerts
|

Del(6)(q22) and BCL6 Rearrangements in Primary CNS Lymphoma Are Indicators of an Aggressive Clinical Course

Abstract: Purpose Primary CNS lymphoma (PCNSL) is an aggressive lymphoma but clinically validated biologic markers that can predict natural history to tailor treatment according to risk are lacking. Several genetic changes including BCL6 rearrangements and deletion of 6q22, containing the putative tumor suppressor gene PTPRK, are potential risk predictors. Herein we determined the prevalence and survival impact of del(6)(q22) and BCL6, immunoglobulin heavy chain (IGH), and MYC gene rearrangements in a large PCNSL cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
5
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 41 publications
4
82
5
1
Order By: Relevance
“…27 Some studies have suggested that patients who harbor such abnormalities have a shorter overall survival. 23,25 In our study, despite the apparent trend toward shorter survival in these patients, the difference was not statistically significant. The lack of statistical significance may be related to the small number of our patient sample.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…27 Some studies have suggested that patients who harbor such abnormalities have a shorter overall survival. 23,25 In our study, despite the apparent trend toward shorter survival in these patients, the difference was not statistically significant. The lack of statistical significance may be related to the small number of our patient sample.…”
Section: Discussioncontrasting
confidence: 79%
“…Earlier studies of primary central nervous system lymphomas in immunocompetent hosts revealed similar rates of MYC/IGH and IGH/BCL2 abnormalities. [23][24][25] Interestingly, both in our study and in earlier reports, the majority of primary central nervous system lymphomas show strong expression of Bcl-2 and C-MYC, indicating that overexpression at protein and mRNA levels is poorly correlated with the rearrangements of BCL2 and C-MYC genes. 25,26 Thirty-three percent (7/21) of cases showed additional signals for IGH, BCL2, and C-MYC.…”
Section: Discussionsupporting
confidence: 62%
“…Interestingly, the loss of the PTPRK locus on 6q22 has been associated with a poor outcome in PCNSL patients in 2 previous studies. However, patient clinical characteristics were not available (39) or treatments not detailed (14,39). In the present study, we observed a significantly shorter PFS and OS in PCNSL patients with 6q22 loss in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the authors showed that chromosome 6q loss was found at a significantly higher rate in PCNSL than in systemic DLBCL and was correlated with shorter survival [22]. An independent study of 75 newly diagnosed HIV-negative PCNSL patients investigated by interphase fluorescence in situ hybridization analysis confirmed frequent del(6)(q22) chromosome deletion, with a prevalence of 45%, and its negative impact on overall survival (OS) [23]. Chromosome 6q loss therefore represents a prognostic marker in PCNSL.…”
Section: Pathology and Pathogenesismentioning
confidence: 99%
“…Chromosome 6q loss therefore represents a prognostic marker in PCNSL. Further, the BCL-6 gene has been found to be mutated and its chromosomal locus (3q27) is often translocated (20%), suggesting that BCL-6 activation through genomic rearrangements may play a role in PCNSL pathogenesis [23][24][25]. BCL-6 is frequently expressed in PCNSL, but there are conflicting data on its prognostic value as an immunohistochemical marker [16, 26 -29].…”
Section: Pathology and Pathogenesismentioning
confidence: 99%